Analysis of Educational Excellence in the 2016-2018 triennium for basic education at the General Santander Educational Institution - Díaz-Pinzón, Jorge Enrique (IJERI: International Journal of Educational Research and Innovation, 2019)
This research work aimed to perform an analysis of educational excellence, Synthetic Index of Educational Quality (ISCE), in the triennium 2016 to 2018, at the General Santander Educational Institution of the municipality of Soacha-Cundinamarca, Colombia. The calculation was made for each of the components of excellence; Progress, Performance, Efficiency and School Environment. It was possible to see an increase in their ISCE from 2016, from 4.20 to 2018 to 4.89. This is due to the improvement plans that the institution has implemented year after year to improve its ISCE.